2021
DOI: 10.7759/cureus.13382
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Patients’ Satisfaction About Telemedicine Used in Saudi Arabia During COVID-19 Pandemic

Abstract: Background Many studies have found that telemedicine and telehealth services quality and patients’ clinical outcomes, following telehealth visits, maybe comparable to those of traditional face-to-face office visits especially in a crisis like COVID-19 complete lockdown. Objective This study aimed to identify the patient's experience in using the telemedicine strategies during the COVID-19 pandemic and assess these patients' perception about their experience of using telemedicin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 24 publications
4
50
3
Order By: Relevance
“…The evidence showed positive results, considering the challenges and limited perspective of clinicians, patients, policymakers, and stakeholders [3,[20][21][22][23][24][25]. Previous national surveys in Saudi Arabia have demonstrated that the DHTPs for COVID-19 have the advantage of wide access, user-friendly interface, ease of use, and high acceptance rate [22][23][24][25][26][27].…”
Section: Determinants For Optimising Dhtpsmentioning
confidence: 99%
“…The evidence showed positive results, considering the challenges and limited perspective of clinicians, patients, policymakers, and stakeholders [3,[20][21][22][23][24][25]. Previous national surveys in Saudi Arabia have demonstrated that the DHTPs for COVID-19 have the advantage of wide access, user-friendly interface, ease of use, and high acceptance rate [22][23][24][25][26][27].…”
Section: Determinants For Optimising Dhtpsmentioning
confidence: 99%
“…A systematic review conducted by Kruse et al revealed that assessing patients’ satisfaction toward telehealth and its associated factors could help stakeholders to find solutions for specific problems [ 15 ]. A recent study by Asma et al in the Kingdom of Saudi Arabia (KSA) reported that nearly one-third (37%) of patients were highly satisfied with the telemedicine services provided to them during the COVID-19 pandemic [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Abdel Nasser et al reported that 53.4% of users were satisfied with the easy registration, while a smaller percentage were satisfied with the audio and video quality of the telemedicine session (40.1% and 41.9% respectively). 14 Finally, in another online survey targeting patients who benefited from virtual clinic services in primary healthcare settings between March and July 2020, 439 patients were identified and factors associated with satisfaction were assessed, with male patients and those with lower education levels being more likely to be satisfied with the virtual clinic services. 15 …”
Section: Introductionmentioning
confidence: 99%